Tradisi Pandhalungan, Nilai Nusantara, dan Pertalian Kebudayaan di Masyarakat Jember - Muhammad Zamroni (Medan Resource Center, 2021)
Indonesia is a rich nation in culture side. The ethnic diversity, local culture, ethnicity, class, and religion, has formed a society distinctive in Indonesia, which made Indonesia has more distinctive features and peculiarities in its various forms than other nations in the world. In addition, the Indonesian people are known for their friendly attitude, helping character, preference of working together and working hand in hand. All these attitudes are coming from natural characters which exist in village communities, which very few belong to the urban community. The evidence that the understanding of Indonesian society is inclusive, moderate and humanist cannot be ignored, because the social culture that grows and develops in Indonesia teaches these traits and attitudes. In the context of rural Indonesian society, especially for Jember society, it is borrowing the term used by Pandhalungan is a cultural identity.